THE USE OF PAIR COMPOSITION METHOD ON STUDENTS’ DESCRIPTIVE WRITING SKILL - Maya Nurmayanti (English Review: Journal of English Education, 2014)
Abstract: This research was aimed to find out roles of pair composition method on students’ behaviour in learning processes and their writing assessment, and also to find out students’ attitude toward learning process of pair composition method in writing descriptive text in the classroom. Descriptive qualitative method was used in this research. The participants were 33 students of X grade of Senior High School. The data were collected from observation, the result of analysis showed that 66% of the seriousness of students during learning process was high, 78% of enthusiasm of students in doing task was high, and 58% of students’ participation was high. The increasing of students’ assessment was 18,7 from the average score before. The data collected from interview and questionnaire indicated that pair composition method provided the opportunities for sharing ideas, developing text, corresting writing errors, motivating students being active, and 50% students strongly agreed that pair composition method on writing descriptive text was lively and enjoyable.Keywords: Active learning strategy, cooperative learning, pair composition method, descriptive writing, descriptive text.